Keramiek in het Stedelijk. - Crommelin, Liesbeth; Fuchs, Rudi H.; Meihuizen, Job (Amsterdam : Stedelijk Museum Amsterdam, 1998)
Brouwer, Willem Coenraad ; Halpern, Lea ; Haagsche Plateelfabriek Rozenburg ; Colenbrander, Theodorus A.C. ; Lion Cachet, Carel Adolph ; Nieuwenhuis, Theodoor Willem ; van der Hoef, Christiaan Johannes ; Bigot, Alexandre ; Decoeur, Emile ; Delaherche, Auguste ; Costa, Joseph Mendes da ; Lanooy, Christiaan Johannes ; Nienhuis, Bert ; Stuart, Sophie Verrijn ; de Blanken, Gerrit ; Hermann Kähler, Nestved ; Onnes, Harm Kamerlingh ; Hubers, Dirk ; Wildenhain, Franz Rudolf ; Pincombe, Helen ; Rie, Lucie ; Coper, Hans ; Pierre, Francine Del ; Picasso, Pablo ; Arabia ; De Porceleyne Fles ; van Loon, Johan ; van der Vaart, Jan ; De Jong, Hans ; Landweer, Sonja ; De Rooden, Jan ; Rolf, Johnny ; Duckworth, Ruth ; Baarspul, Adriana ; Mutsaerts, Ankie ; Drescher, Trudy ; Oestreicher, Helly ; Giles, Maggi ; Gommans, Huub ; Voulkos, Peter ; Arneson, Robert ; Price, Ken ; Gilhooly, David ; Nagle, Ron ; Shaw, Richard ; Britton, Alison ; McNicoll, Carol ; Poncelet, Jacqui ; Slee, Richard ; Smtih, Martin ; Culot, Pierre ; van der Waerden, Anne ; Lap, Geert ; Haenen, Babs ; Lichtveld, Alexander ; Nanning, Barbara ; Marinus, Kees ; Henderson, Ewen ; Lord, Andrew ; Pöschl, Veronica ; Vonck, Irene ; Stockmans, Piet ; van den Heuvel, Netty ; Nielsen, Niels ; Sottsass, Ettore ; Mollema, Roel ; Blits, Mieke ; Förg, Gunther ; Woodman, Betty
biografie
Nederlands & Engels
boek